Research progress on natural products in regulating the gut microbiota in Parkinson’s disease - Jia, Ying; Zhang, Yuanyuan; Tai, Xin; Zhao, Tengyu; Zhang, Hanwen; Zhou, Haichun (Frontiers in Pharmacology, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder associated with α-synuclein deposition and dopaminergic neuron degeneration. Recent studies have revealed a close correlation between gut microbiota dysbiosis and the pathogenesis and progression of PD. Gut microbiota may influence the disease through multiple pathways, including promoting α-synuclein pathology, disrupting the gut-brain barrier, and triggering inflammation and neuronal damage. Currently, drug treatments for PD primarily focus on compensating for dopaminergic neurotransmission deficits, delaying neuronal degeneration, and clearing abnormal protein aggregates. However, these drugs can only slow disease progression and are associated with significant adverse effects. In contrast, natural products exhibit distinct advantages in modulating PD pathological features by targeting the “gut microbiota-metabolite axis,” owing to their multi-target synergistic regulation and favorable safety profiles, making them an ideal strategy for PD intervention. Based on this, we provide a comprehensive review of natural products that regulate the gut microbiota, analyze their specific mechanisms, and offer novel insights into this approach and provide a theoretical foundation for developing safe and effective PD therapeutics.